(untitled) (Law, State and Telecommunications Review, 2024)
[Purpose] The text addresses the contracting of additional services in telecommunications, in relation to the judgment of the Supreme Court of Justice of 2 February 2022 (case no. 22640/18.1T8LSB.L1.S1), which applied the legal regime of general contractual clauses and the prohibition of aggressive commercial practices. The aim is to deepen the debate on these institutes, contributing to the study of their repercussions on the protection of consumers’ economic interests. [Methodology/Approach/Design] Analysis of the reasoning adopted by Portuguese case law, as well as the relevant legislation and doctrine regarding the contracting of additional services in telecommunications. [Findings] The text demonstrates the pioneering and innovative nature of the judgment in effective consumers protection in Portugal, predicting that the reasoning may also be followed in other comparative law systems, since it is mostly based on legislation resulting from the transposition of European Directives.